The criteria for ranking and prioritization of rehabilitation of abandoned mines - Sphiwe Emmanuel Mhlongo; Sibulele Sigxashe (Journal of Degraded and Mining Lands Management, 2021)
The rehabilitation of abandoned mines begins with the characterization and ranking of these mines. Based on this, countries, organizations, and individual researchers have developed tools for ranking abandoned mines for rehabilitation. This paper comments on the issues of abandoned mines which include their definition and the problems they possess. It then critically examines the criteria used by different tools to prioritize the rehabilitation of abandoned mines. It showed that there is a sharp increase in the number of academic tools developed for the ranking of abandoned mines over the years. These tools demonstrated how the parameters disregarded in official ranking tools can rank the abandoned mines for rehabilitation. The paper recommends that the main issues of abandoned mines and their rehabilitation be part of the criteria of ranking these mines for rehabilitation. The inclusion of such parameters in the ranking criteria promises to improve the accuracy of the ranking process. It will go a long way in ensuring that the ranking tools provide the correct advice on what strategies can be used to rehabilitate these mines.